Diuron degradation by bacteria from soil of sugarcane crops - Egea, Tassia C. [UNESP]; da Silva, Roberto [UNESP]; Boscolo, Maurício [UNESP]; Rigonato, Janaina; Monteiro, Diego A. [UNESP]; Grünig, Danilo; da Silva, Humberto [UNESP]; van der Wielen, Frans; Helmus, Rick; Parsons, John R.; Gomes, Eleni [UNESP] (Elsevier, 2017)
The isolation of microorganisms from soil impacted by xenobiotic chemicals and exposing them in the laboratory to the contaminant can provide important information about their response to the contaminants. The purpose of this study was to isolate bacteria from soil with historical application of herbicides and to evaluate their potential to degrade diuron. The isolation media contained either glucose or diuron as carbon source. A total of 400 bacteria were isolated, with 68% being Gram-positive and 32% Gram-negative. Most isolates showed potential to degrade between 10 and 30% diuron after five days of cultivation; however Stenotrophomonas acidophila TD4.7 and Bacillus cereus TD4.31 were able to degrade 87% and 68%, respectively. The degradation of diuron resulted in the formation of the metabolites DCPMU, DCPU, DCA, 3,4-CAC, 4-CA, 4-CAC and aniline. Based on these results it was proposed that Pseudomonas aeruginosa TD2.3, Stenotrophomonas acidaminiphila TD4.7, B. cereus TD4.31 and Alcaligenes faecalis TG 4.48, act on 3,4-DCA and 4-CA by alkylation and dealkylation while Micrococcus luteus and Achromobacter sp follow dehalogenation directly to aniline. Growth on aniline as sole carbon source demonstrates the capacity of strains to open the aromatic ring. In conclusion, the results show that the role of microorganisms in the degradation of xenobiotics in the environment depends on their own metabolism and also on their synergistic interactions.
Keywords: Environmental sciences; Microbiology